Axiological status of lexems CHASTE, CHASTITY, and VIRGINITY in Ukrainian media discourse - Levko, Oleksandr (Current issues of Ukrainian linguistics: theory and practice, 2018)
The paper addresses the use of the words цнотливий, цнотливість and цнота in the Ukrainian political media discourse, with a particular focus on the evolution of the "chastity words" semantics in the Ukrainian language, based on social and political publications of the internet portals "Dzerkalo tyzhnja", "Ukrajinskyj Tyzhden", "Ukrajinska Pravda". The canon of Christian virtues, established in the Middle Ages, is no longer accepted unquestioningly by modern society, and thus it is not surprising to see an ambivalent attitude to certain religious ascetic virtues, e.g. chastity, humility, piety etc. It is revealed that evaluative semantics of the "chastity words" in the Ukrainian political media discourse varies for different reference groups such as "women", "men", "girls", "boys", "state", "politicians", "language", "literature", "art" and "cinema". When denoting female virtue, the "chastity words" have positive and neutral connotations. It is shown that chastity as a virtue of men and women is synonymous in the Ukrainian media discourse to modesty, decency, morality, honor, dignity and virtue. “Chaste" as a characteristic of an intimate contact indicates its tenderness and decency, which is positively assessed by the participants of communication in Ukrainian political media discourse. The use of the "chastity words" as an attribute of government and public institutions is conditioned by a cognitive metaphor, where the source domain is a woman or an intimate relationship. The language evaluation of the "chastity words" ranges from positive to extremely negative in the political media texts: in the latter case they acquire negative evaluative meanings "stagnation", "limitation", "ideological engagement," "conservatism," "lack of reform." Sometimes the "chastity words" acquire negative connotations when attributed to art, literature and cinema, actualizing the semes "lack of progress", "backwardness". In a literal sense, chastity as absence of excessive eroticism and moral debauchery in art and films is evaluated positively in the Ukrainian social and political media discourse.